2014
DOI: 10.1177/082585971403000303
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Fulfilling the Preference for Dying at Home among Cancer Patients: The role of General Practitioners

Abstract: Aim: This study aimed to explore clinical and care-related factors associated with fulfilling cancer patients' preference for home death across four countries: Belgium (BE), the Netherlands (NL), Italy (IT), and Spain (ES). Methods: A mortality follow-back study was undertaken from 2009 to 2011 via representative networks of general practitioners (GPs). The study included all patients aged 18 and over who had died of cancer and whose home death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…The overall percentage of deaths in the preferred place was 68.7%; this is lower than the percentages of between 83% and 88% for deaths in the preferred place reported by earlier studies conducted in the Netherlands. [2,7,8,19] This could be a result of the fact that this study was carried out among bereaved relatives of patients with various diseases, whereas earlier studies mainly covered cancer patients; a cancer diagnosis is associated with a greater likelihood of dying in the preferred place. [12] It is noteworthy that, at the univariate level, our analysis showed that cancer patients were more likely to die in the preferred place than patients with dementia and organ failure diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall percentage of deaths in the preferred place was 68.7%; this is lower than the percentages of between 83% and 88% for deaths in the preferred place reported by earlier studies conducted in the Netherlands. [2,7,8,19] This could be a result of the fact that this study was carried out among bereaved relatives of patients with various diseases, whereas earlier studies mainly covered cancer patients; a cancer diagnosis is associated with a greater likelihood of dying in the preferred place. [12] It is noteworthy that, at the univariate level, our analysis showed that cancer patients were more likely to die in the preferred place than patients with dementia and organ failure diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other research also identified provision of palliative care by the GP as a factor associated with a congruence between the actual and preferred place of death. [8] The causality of this relationship, however, needs to be further investigated.. Coordination between all professionals involved is important, as this is also associated with dying in the preferred place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cancer progresses, patients often express a preference to receive care at home and to die at home, if possible, 456 which may be facilitated by PPC providers. 457 In addition, these physicians support families during bereavement, offering excellent continuity of care that is highly valued by patients and their families. 458 There is wide variability internationally in the engagement of family physicians and general practitioners in palliative care from less than 50% in some countries such as Canada and Japan, 459,460 to up to 85% in the United Kingdom, the Netherlands and Australia.…”
Section: Figure 3: Conceptual Model Of Palliative Care Delivery Basedmentioning
confidence: 99%
“…Badrakalimuthu and Barclay, 2014;Calanzani et al, 2014;Campbell et al, 2014;Chen et al, 2014;De Roo et al, 2014;Fleet et al, 2014;Gomes et al, 2012;Hedinger et al, 2014;Hunt et al, 2014;Ko et al, 2014;Lee et al, 2014;McHugh et al, 2014;Reyniers et al, 2014;Venkatasalu et al, 2014); this is a rapidly expanding area of interest. However, surprisingly little has been written about the experience of the surroundings in which dying and death take place.…”
Section: Introduction and Aimmentioning
confidence: 96%